Interfering Influences on Electrical Cable between Frequency Converter and Electric Motor - Sadílek, Ondřej; Lelek, Tomáš; Kořínek, Jan (IEEE (Institute of Electrical and Electronics Engineers), 2016)
The paper presents the results of the experiments aiming at the quantitative assessment of the adverse effects that arise when the electric drive is powered by the alternating current (AC) power via a long cable. For elimination of negative influences were used various types of output EMI (electromagnetic interferences) devices. It was studied, how much mention devices reduce interfering influences – mainly overvoltage peaks and rate of voltage rise.
Rušení na elektrickém kabelu mezi frekvenčním měničem a elektrickým motorem
Keywords: EMC; overvoltage; frequency converter; output reactor; PWM; EMC; přepětí; frekvenční měnič; výstupní tlumivka; PWM